Expression of ACKR2 in placentas from different types of preeclampsia. (15th January 2020) - Yan, Shujun; Cui, Shihong; Zhang, Linlin; Yang, Bo; Yuan, Yangyang; Lv, Xiaofeng; Fu, Han; Li, Yingying; Huang, Chenxi; Wang, Ping
Abstract: Objective: The purpose of this study was to investigate the expression of atypical chemokine receptor 2 (ACKR2, D6) in different types of preeclampsia (PE) and its effects on trophoblast proliferation and apoptosis. Methods: The subjects were divided into four groups: early-onset PE group (EOPE, n = 30), late-onset PE group (LOPE, n = 30), preterm birth group (PB, n = 30), and normal group (N, n = 30). The expression of ACKR2 in placentas was evaluated using immunohistochemistry, qRT-PCR, and Western blot. The trophoblast cell line JAR was cultured to detect the expression of ACKR2 after simulating hypoxic conditions with cobalt chloride (CoCl2 ). The effects on cell proliferation, apoptosis, and expression of the chemokine CCL2 were analyzed after silencing ACKR2 with siRNA. Results: ACKR2 was decreased in placentas of EOPE and PB groups at the protein and mRNA level，compared to the normal group. No statistical differences were found between EOPE and PB groups, or between LOPE and normal groups. In our in vitro work, we found that the expression of ACKR2 decreased after treatment with 150 μmol/L, 200 μmol/L, and 250 μmol/L of CoCl2 . After ACKR2 was silenced, the degree of cellular proliferation decreased, while apoptosis and CCL2 expression increased. Conclusion: The changes of ACKR2 expression in placentas of PE may be related to gestational weeks. Hypoxia inhibits the expression of ACKR2 in placentas. Abnormal expression of ACKR2 in PE may lead to dysfunction of trophoblast, and ACKR2 is an essential player in the immunoregulation of the placental chemokine CCL2. Highlights: ACKR2 mRNA decreases in placentas from early-onset preeclampsia. ACKR2 protein expression decreases in placentas from early-onset preeclampsia. Hypoxia can inhibit the expression of ACKR2. When ACKR2 is silenced in trophoblast, cell apoptosis increases. After ACKR2 is silenced in trophoblast, the expression of chemokine CCL2 increases.